An Evaluation Of The Treasury Single Account (TSA) As An Instrument Of Financial Prudence and Management In Nigeria: Methodology Analysis (OAGF) 2015-2024. - Sulaiman Taiwo Hassan; Iyere Samuel Iheonkhan; Ma. Viktoria Monique M. Hawod; Franchezka Nicole L. Calicdan; Pauline Kate M. Coronel (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This paper examines the Office of the Accountant General of the Federation and the relationship between the Nigerian economy and the Treasury Single Account Policy (2015-2024). The Nigerian economy has developed slowly over the years, which has led to little to no improvement in the country's residents' standard of living. The study's overall goal was to determine how the Treasury Single Account Policy affected Nigeria's economic developments between 2015 and 2024. Its specific goals were to determine whether the human development index, Gini coefficient, and poverty rate of the country's economy differed significantly between the pre-and post-implementation periods. The research utilized the design of the quantitative study. Nigerian citizens make up the study's population, while the citizens of Nigeria for the years 2015–2024 make up the sample size. The study employed secondary data that came from the World Bank's National Accounts Data, the National Bureau of Statistics, and the Central Bank of Nigeria's Statistical Bulletin. The paired sample t-test was used to assess the data. The outcome showed that, except the variable of human development index, which showed a significant difference between the periods before and after the implementation of the treasury single account policy, economic development indicators (gini coefficient and poverty rate) did not differ significantly between the periods before and after the policy. Consequently, the analysis found that the Treasury Single Using the poverty rate and Gini coefficient as stand-ins for economic development, account policy had no discernible effect on the Nigerian economy. Additionally, it was determined that the Treasury Single Account Policy had a major influence on Nigeria's economic development using the Human Development Index as a proxy for economic progress. Therefore, it was advised that government programs for human development be maintained and improved, particularly in the fields of health and education.